Plan de gestión emergente de Residuos Sólidos para la ciudad de Paccha, cantón Atahualpa, El Oro - Guzmán Sánchez, Jenny Verónica (My University, 2021)
Since the beginning of the man, we can inherently find that solid waste is the product of everyday activities. Currently, with the accelerated population growth and industrialization, the accumulation of waste has become a difficult problem to solve. In Ecuador, 12,671.18 tons of solid waste are generated daily, according to reports from the municipal governments, 48.2% is disposed of properly, 32.7 % is disposed of in emerging cells and 19.1% is disposed of in open dumps, incinerators or rivers. The present work consists of a solid waste management plan for the city of Paccha that addresses several proposals in response to the inefficient solid waste disposal process. To achieve this objective, it is necessary to implement environmental education programs, segregation and storage of solid waste, family gardens, extension of the useful life of the landfill, and closure of the landfill. The purpose of each of these programs is to reduce the environmental impact and improve the quality of life.
A partir de la existencia del hombre, podemos encontrar inherentemente que los residuos sólidos son el producto de actividades cotidianas. En la actualidad, con el acelerado crecimiento demográfico y la industrialización; la acumulación de desechos se ha convertido en un problema difícil de resolver. En el Ecuador se genera diariamente 12.671,18 toneladas de residuos sólidos, según informe de los GAD Municipales, el 48.2% cuenta con una adecuada disposición final, el 32.7 % en celdas emergentes y el 19.1% tiene como destino botaderos a cielo abierto, incineradores o ríos. El presente trabajo consiste en un plan de gestión de residuos sólidos para la ciudad de Paccha que aborda varias propuestas como respuesta al ineficiente proceso de disposición final de residuos sólidos. Para lograr este objetivo es necesario la implementación de programas de educación ambiental, segregación y almacenamiento de residuos sólidos, huertos familiares, prolongación de la vida útil del relleno sanitario y clausura de este. El propósito de cada uno de ellos es reducir el impacto ambiental y mejorar la calidad de vida.
Keywords: EMERGENTE; DISPOSICION FINAL